2002
DOI: 10.1067/mcp.2002.126913
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 phenotypic ratios for predicting herb‐drug interactions in humans

Abstract: Single-time point phenotypic metabolic ratios may provide a practical means of predicting CYP-mediated herb-drug interactions in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
256
2
9

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(289 citation statements)
references
References 59 publications
(72 reference statements)
22
256
2
9
Order By: Relevance
“…These results are consistent with a previous report that showed no changes in the pharmacokinetics of the CYP3A4 substrates, midazolam and alprazolam (Markowitz et al, 2003, Gurley et al, 2005, Gurley et al, 2002. Therefore, our results demonstrate a differential induction of PGP and CYP3A4 in response to garlic extract, suggesting that garlic extract can induce intestinal PGP independent of effecting CYP3A4.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are consistent with a previous report that showed no changes in the pharmacokinetics of the CYP3A4 substrates, midazolam and alprazolam (Markowitz et al, 2003, Gurley et al, 2005, Gurley et al, 2002. Therefore, our results demonstrate a differential induction of PGP and CYP3A4 in response to garlic extract, suggesting that garlic extract can induce intestinal PGP independent of effecting CYP3A4.…”
Section: Discussionsupporting
confidence: 82%
“…Currently, there are three studies that have investigated the effects of garlic on CYP450 drug metabolizing enzymes in humans (Gurley et al, 2002, Markowitz et al, 2003, Gurley et al, 2005. Using debrisoquine, midazolam, caffeine, and chlozoxazone as test substrates, Gurley et al showed that garlic oil decreases CYP2E1 activity by 39% and 22% in young and elderly volunteers, respectively, yet exhibits no effect on CYP1A2, 2D6, and 3A4 function (Gurley et al, 2002, Gurley et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the CAR activators, phenobarbital and 1,4-bis-[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP) demonstrate male-specific Cyp2a4 induction (Wei et al, 2002). Lastly, St. John's wort mediated induction of CYP3A4 is greater in human females than males (Gurley et al, 2002). Gender differences in P450 induction are important to discern because of potential gender-specific side effects following pharmaceutical or environmental chemical exposure (Meibohm et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many herbal and dietary products modulate cytochrome P450 activity. Gurley et al (2002) used single-time point phenotypic metabolic ratios to determine whether long-term supplementation of St John's wort, garlic oil, P. ginseng and Ginkgo biloba affected CYP1A2, CYP2D6, CYP2E1 and CYP3A4 activities in humans; no significant effect was observed for P. ginseng. In agreement with this, Gurley et al (2005) observed that the concomitant ingestion of P. ginseng with prescription medications in elderly patients resulted in only slight inhibition (7%) of CYP2D6 activity.…”
Section: Antigenotoxic Effects Of Panax Ginseng 949mentioning
confidence: 99%